Is There a Balance in Oxidative-Antioxidant Status in Blood Serum of Patients with Advanced Endometriosis? - Kokot, Izabela (Antioxidants (Basel), 2021)
Can redox homeostasis indicators be potential non-invasive markers, crucial in the diagnosis and treatment of endometriosis? We checked if the differences in levels of serum oxidative-antioxidant balance parameters (TAS, FRAP, albumin, total bilirubin, uric acid, iron, SIRT3, SIRT5, SIRT6, telomerase, AOPP) are significant between patients with advanced endometriosis (E), healthy women (control group, C) and non-endometriosis women, but with other gynecological disorders (NE). The FRAP concentrations were significantly higher in E and NE group than in the control group (p = 0.015 and p = 0.017, respectively). The telomerase concentrations were significantly higher in the endometriosis group than in the control group (p = 0.004). Significantly higher concentrations of AOPP were observed in E (p < 0.001) and NE groups (p = 0.028) in comparison to the control subjects. Between stages III and IV of endometriosis, a significant difference existed only in concentration of iron (p = 0.013). There were no significant differences between the studied groups in the values of the remaining parameters. Based on the results of ROC curve analysis, we can conclude that the levels of serum FRAP, telomerase and AOPP may be taken into account as promising diagnostics markers that reflect the degree of oxidative stress accompanying advanced endometriosis.